Toxicological and Nutritional Characterization of Hydro-methanolic Carica papaya Leaf Extract in Wistar Rats - ANYIA, Francis Agwanyeokhai; Elekima, Ibioku; Onwuli, Donatus; Nwachuku, Edna Ogechi (Journal of Disease and Global Health, 2026)
Carica papaya (C. papaya Linn) is a medicinal plant that is well researched and documented for its many pharmacological properties, including antioxidant and anti-inflammatory properties; it is also believed to be rich in essential minerals, nutrients and food substances. In this study, the Maximum Tolerable Dose of the hydro-methanolic leaf extracts, selected mineral elements, selected heavy metals, total, essential and non-essential amino acids, and the proximate composition of the leaves of Carica papaya were determined. The leaves were harvested in triplicate from three (3) different farms in Rumuekini, Obio-Akpor Local Government Area, Rivers State, Nigeria, West Africa, and the plant leaves were identified in the Department of Plant Science and Biotechnology, University of Port Harcourt, Rivers State. The Maximum Tolerable Dose (MTD) procedure used a staged acute-toxicity approach adapted from Chinedu et al. (2013), with reference to Lorke (1983) and OECD Test Guideline 425 (OECD, 2022). The hydro-methanolic leaf extraction was performed using the Soxhlet method according to the standard method described by Sofowora (1981). Selected mineral elements (Sodium, Potassium, Magnesium, Iron, Selenium, Calcium & Copper) and heavy metals (Cadmium, Lead, Nickel, Chromium, Aluminum, Arsenic & Mercury) in the leaves of C. papaya were assessed using an atomic absorption spectrophotometer (AAS), Agilent FS 240 AA. The total, essential and non-essential amino acids were determined using Gas Chromatography Flame Ionization Detection (GCFID), Agilent 6890 technologies. The proximate analysis was performed using the AOAC method. The mineral element, heavy metal, amino acid and proximate analyses were performed on leaves harvested from the three (3) farms. The results revealed that the MTD for the hydro-methanolic leaf extracts of C. papaya was 5,000 mg/kg b. wt. Among the mineral elements in C. papaya, Sodium (10.68 ± 0.62 ppm) was the most concentrated; other elements included Calcium (8.23 ± 0.14 ppm), Potassium (6.95 ± 0.18 ppm) and Magnesium (6.27 ± 0.14 ppm). The heavy metal composition of the leaves of C. papaya included Lead (0.11 ± 0.00 ppm), Arsenic (0.07 ± 0.00 ppm) and Cadmium (0.02 ± 0.00 ppm). The heavy metals determined were within WHO permissible limits. The amino acid analysis revealed a total amino acid level of 78.29 ± 1.18 mg/kg; other amino acid fractions included Serine (11.50 ± 0.06 mg/kg) and Threonine (10.15 ± 0.06 mg/kg). The proximate analysis revealed Carbohydrate (41.39 ± 1.18%), Protein (24.78 ± 0.96%), Crude Fiber (14.74 ± 0.46%) and Crude fat (7.26 ± 0.28%). Hence, the leaves of Carica papaya were non-toxic, safe and non-lethal at 5,000 mg/kg b. wt. The heavy metals were within WHO acceptable limits, and the leaves were a rich source of mineral elements, amino acids (Essential and Non-Essential), and stable food materials (Carbohydrates, Proteins, etc.). Therefore, Carica papaya leaves could be incorporated as a drug, supplement or nutraceutical for human and mammalian use.